Welcome to Westonci.ca, your one-stop destination for finding answers to all your questions. Join our expert community now! Join our Q&A platform to get precise answers from experts in diverse fields and enhance your understanding. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Answer:
y = 6
x = 5
Step-by-step explanation:
-6x + 6y = 6
-6x + 3y = - 12
Multiply the second equation by -1, then add the equations;
-6x + 6y = 6
6x - 3y = 12
___________
3y = 18
/3 /3
y = 6
x = 5
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.